Pelatihan Volunteerism pada Remaja - Ahmad Ridfah; Nur Afni Indahari; Wawan Kurniawan (DEDIKASI, 2018)
In this volunteerism training, 25 participants who were high school students were given material related tovolunteerism, especially volunteerism in the field of literacy. Participants who are in adolescence are classified assensitive to the social processes that occur. This training is expected to help improve the ability and usefulness ofadolescents for others, this can be seen from the increase in motivation to volunteer to participants. The training washeld for four days. After the training ended, it was obtained data that the motivation to become a volunteerincreased, as well as the volunteering outcomes of the participants